Dominica : 2007 Article IV Consultation-Staff Report; Staff Supplement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2007)
This 2007 Article IV Consultation highlights that Dominica has fully recovered from the 2001-02 economic and financial crisis. Output growth has rebounded, reaching 4 percent in 2006, and it is expected to remain above trend in 2007. The rebound is driven by a pickup in tourism, recovery in banana production, and buoyant construction and offshore school activity. Inflation has remained subdued, reflecting stabilizing oil prices, and is projected to remain low. The external current account deficit narrowed sharply in 2006, and is likely to remain large at about 20 percent of GDP in 2007.